2009
DOI: 10.1021/ac9001047
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Characterization of Solid Epoxy Resins Using Comprehensive Two Dimensional Liquid Chromatography Coupled with Electrospray Ionization-Time of Flight Mass Spectrometry

Abstract: A comprehensive multidimensional liquid chromatography system coupled to Electrospray Ionization-Mass Spectrometry (LCxLC-ESI-MS) was developed for detailed characterization and quantitation of solid epoxy resin components. The two orthogonal modes of separation selected were size exclusion chromatography (SEC) in the first dimension and liquid chromatography at critical conditions (LCCC) in the second dimension. Different components present in the solid epoxy resins were separated and quantitated for the firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Nevertheless, SEC has also been applied as 1 D separation. Examples include SEC × RPLC [135] and SEC × LCCC [135,136]. Readers interested in LC × LC separations of synthetic polymers and oligomers are referred to the review by Uliyanchenko et al [137].…”
Section: Size-exclusion Chromatography and Hydrodynamic Chromatographymentioning
confidence: 99%
“…Nevertheless, SEC has also been applied as 1 D separation. Examples include SEC × RPLC [135] and SEC × LCCC [135,136]. Readers interested in LC × LC separations of synthetic polymers and oligomers are referred to the review by Uliyanchenko et al [137].…”
Section: Size-exclusion Chromatography and Hydrodynamic Chromatographymentioning
confidence: 99%
“…Ideally the distribution should be discrete weights separated by multiples of 284 g/mol, the value of the repeat unit in Figure (A). While the ideal structure may be present for the lower molecular weight epoxies, the ideal di‐functional form is not always present in higher molecular weights as shown by Julka et al who tentatively identified nine types of nonideal species, with one to three epoxy groups in solid epoxies . These combine to result in the mismatch between the titration and GPC results.…”
Section: Resultsmentioning
confidence: 99%
“…This procedure was first applied by Balke in 1982 [94] and was later elaborated by Pasch [48,95,96], Kilz [97,98] and others [99][100][101][102][103]. For polymers soluble at room or elevated temperatures, many examples of 2-D LC separation exist.…”
Section: -D Lc For Polyolefinsmentioning
confidence: 99%
“…Coupling of two different chromatographic systems enables to resolve multiple distinctive components 93. This procedure was first applied by Balke in 1982 94 and was later elaborated by Pasch 48, 95, 96, Kilz 97, 98 and others 99–103. For polymers soluble at room or elevated temperatures, many examples of 2‐D LC separation exist.…”
Section: Molecular Characterization Of Polyolefinsmentioning
confidence: 99%